Naples Yellow Revisited: Insights into Trades and Use in 17th-Century Sicily from the Macro X-ray Fluorescence Scanning of Matthias Stomer’s ‘The Mocking of Christ’ - Michela Botticelli; Costanza Miliani; Eva Luna Ravan; Claudia Caliri; Francesco Paolo Romano (Heritage, 2024)
In a recent non-destructive analytical campaign at Museo Civico, Castello Ursino, in Catania, Italy, several paintings in the permanent collection were investigated by MA-XRF scanning, with a special focus on Matthias Stomer’s production. On one depiction of the Mocking of Christ (ca. 1640) donated to the municipality of Catania by G.B. Finocchiaro in 1826, the analysis documented the use of Naples yellow. Sb with Pb was detected in yellow areas of the Mocking of Christ, but not in his work Tobias healing his father. This finding possibly suggested an early use of lead antimonate yellow in South Italy, although it is generally accepted that this pigment was introduced in painting in the eighteenth century. Further details on his technique and later conservation treatments are provided, as well as literary comparisons with the artistic production during the same period, in Sicily and elsewhere. A systematic study of Stomer’s works, for example examining paintings produced while he was in Naples or Rome, might determine whether this material choice depended on local availability. Overall, it would shed light on his technique, as well as on the history of Naples yellow in southern Italy and beyond, before this pigment became so popular in the eighteenth century.